Nutrition and Fitness Mental Health - Dalle Grave, Riccardo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Mens sana in corpore sano (a healthy mind in a healthy body) is a Latin phrase taken from Giovenale (Satire, X, 356) that remains relevant and is supported by today's data regarding genetics and nutrition, and their contribution to mental health. The purpose of this Special Issue on "Nutrition and Fitness: Mental Health" is to provide an update on the latest evidence regarding the association between nutrition, physical activity (and inactivity) and physical fitness, and the mental health of children, adolescents, and adults. Particularly, papers (reviews and clinical or experimental studies) dealing with the association between nutrition, physical fitness, and mental health both in general and with regard to specific mental disorders, and nutrients and physical activity as agents for prevention, treatment, or augmentation of treatment for mental disorders, will be included.